Opening configurations and natural cross ventilation performance in a double-loaded multi-level apartment building: a CFD analysis - Fu, Xiaohui; Tai, Vin Cent; Moey, Lip Kean; Abd Rahman, Nor Faiza; Ahmad, Kamarul Arifin; Baglee, David (Elsevier, 2024)
This study investigates the impact of varied opening configurations on natural cross ventilation of a double-loaded multi-level apartment. Using computational fluid dynamics (CFD) simulations, twenty-five building models with combinations of top-top (TT), top-bottom (TB), center-center (CC), bottom-bottom (BB), and bottom-top (BT) opening configurations were analyzed in both windward and leeward building blocks. In the windward block, the BB configuration yielded the highest dimensionless flow rate (DFR) for levels 1–3, and BT was highest for levels 5 and 6. Air Exchange Efficiency (AEE) was optimal at 45–55% for TB configurations on levels 1–3, and for CC and BT on levels 4–6. Factor optimization (α) was introduced to balance DFR and AEE, favoring TB configurations for level 1–3 and BT configurations for levels 4–6. Additionally, the leeward block's ventilation was slightly influenced (±3.5%) by the windward block's configurations. Notably, the TT configuration achieved the highest α score at level 1 and TB at level 2, even with the lowest DFR. Conversely, the CC configuration, while having the lowest AEE for the first two levels, yielded the highest DFR values. Bottom inlet configurations recorded the lowest α scores for levels 3–6. The research suggests that the TT and CC configurations are the most effective for ventilation in the leeward block. The results indicate that building design can be optimized for ventilation performance at each level without significant impact to adjacent structures. This informs improved ventilation strategies in high-rise buildings, emphasizing design adaptability to enhance indoor air quality.